A pH sensor based on a stainless steel electrode electrodeposited with iridium oxide - Mayorga Martinez, Carmen Clotilde (2009)
A simple procedure to make an iridium oxide (IrO2) electrodeposited pH sensor, that can be used in a chemical, biomedical, or materials laboratory, is presented here. Some exercises, based on this sensor, that can be used to teach important concepts in the field of biomedical, biochemical, tissue, or materials engineering, are also presented. This novel procedure is based on the electrodeposition of IrO2 on a stainless steel electrode, which uses a similar mechanism to an ion selective electrode (ISE) and senses changes in pH. The simplicity and cost effectiveness of this method facilitates the teaching of the concept of half-cell potential and the basics of sensors. This novel sensor has also been shown to outperform the classical glass pH-sensor. In this new methodology, students learn to build the electrode, to calibrate it, and to measure its sensitivity, repeatability, and time-response. © 2008 IEEE.